Synthesis of Lithium-Aluminum Layered Double Hydroxide Adsorbent from Aluminum Waste to Create a More Environmentally Friendly Process for Recovering Lithium in Brine - Salafudin, Salafudin; Prasetya, Agus; Warmada, I Wayan; Petrus, Himawan Tri Bayu Murti (Indonesian Journal of Chemistry, 2025)
All countries pledged to strive to limit global warming. The implementation of renewable energy must be accelerated. One of the most essential components of renewable energy is lithium-ion batteries. The surging demand for lithium necessitates new technologies for direct recovery from brine. One of the most promising methods is adsorption. Because of its advantages, lithium-aluminum layered double hydroxides have started their application on a commercial scale. This research uniquely explores the synthesis of lithium adsorbent from aluminum waste, an approach that is both cost-effective and environmentally sustainable. The reaction behavior was studied, including the rate of hydrogen gas production and the co-precipitation process. The quality of the product was assessed by its adsorption capacity and characterization. The synthesis of lithium adsorbent was successfully performed through two-step processes, with the reaction kinetics studied at temperatures between 30 and 60 °C. XRD and FTIR results confirmed the adsorbent product. The adsorbent worked well for synthetic brine with 39–1350 ppm lithium concentration and adsorption capacity until 6.7 mg lithium ion per g of adsorbent. These findings contribute to the development of sustainable technologies for lithium extraction and can be applied to improve industrial lithium recovery processes.